如何在疫情中幫助長者面對死亡？香港基督徒的倫理困擾: How to Help the Elderly Cope with Death and Dying during the Pandemic? The Moral Dilemma of Hong Kong Christians - WU, Carrie Ho Yee (International Journal of Chinese & Comparative Philosophy of Medicine, 2021)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 自17世紀以來，基督教信仰一直對香港産生重大影響。從那時起，許多醫院和組織都秉持基督教倫理精神來幫助有需要的人。尤其是臨終的關懷。在過去的一年半Covid-19疫情中，建立多年的醫療系統面對非常嚴峻的挑戰。對於在香港醫院面臨死亡的老人及其家人來説，尤其困難。本文研究了基督教信仰中“善終”的概念，以及老年人及其家人在這個疫情時期面臨的道德困境。作者認為，患者和家屬從身體到靈性需求不應該以公共衛生的名義被犧牲掉。在疫情中，我們更需要基督教的精神和關懷倫理。 Christian faith has been a crucial influence on the cultural and ethical formation of Hong Kong since the 17th century, and many hospitals and institutions for elderly palliative care are associated with Christian churches. However, the past one and a half year have been a challenge because of the global covid-19 pandemic. The situation has been particularly difficult for the elderly facing their death as well as for their family members. This paper therefore investigates the concept of a “good death” in Christian ethics and how Christians should practice the ethic of care during the pandemic. The author contends that we should not ignore the great physical and mental needs of these elderly people and their families in the name of public health concerns.